Crisis four eaudiobook - McNab, Andy (Nick Stone, 2000)
A former member of the UK's elite Special Air Service, the SAS, this best-selling author has seen action on five continents. His thrillers are so chillingly authentic that he is the first British author ever required to submit one of his novels to the British Ministry of Defense for review. Nick Stone, highly trained by the SAS to be methodical and ruthless, now works as a secret agent in "deniable" operations. His current assignment is to hunt down and kill Sarah, the only woman he has ever cared for. But in order to fulfill his mission, he first has to help her escape from the members of a conspiracy to which only she holds the key. Fleeing with Sarah through the backwoods of the American South, Nick is headed for a confrontation beyond anything he could have imagined. Prepare for a new kind of listening experience where violence and cunning are so real that you have to keep reminding yourself this is only fiction. Narrator Steven Crossley's unrelenting pace perfectly reflects the tone of this compelling thriller.